Remediasi Lahan Berpasir di Waisamu yang Ditanami Jagung Lokal melalui Aplikasi Kompos Ela Sagu - Aurellia Tatipata; A. Jacob (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2013)
Soil in Waisamu in generally was sandy and grow with Imperata cylindrica. The aim of our experiment were to sandy soil remedied through ela sagu compost, increase growth and production of local corn. The experiment was important in attempting to make the best of sandy soil function become agriculture soil, in order to cultivate and increasinggrowth and production of local corn to improve the sustanaibility of food supply.The experiment was conducted in Waisamu and consisted of two factors and three replications, using Randomized Complete Block Design. The first factor was compost dosage, consisting of five levels, i.e. 0 ton per hectare, 7.5 ton per hectare, 10 ton per hectare, 12.5 ton per hectare, 15 ton per hectare. The second factor was delima corn. The variables observed for compost quality were C/N ratio, mineral content N, P, K, Ca, Mg, Fe, and initial macro and micro nutrient of soil. Height and leaf area of plant, length, weigh, diameter of corn ear and weight of dry shelled were observed for growth and production of plant. The results proved that C-organic content, macro and micro nutrient in compost can increase organic substance, macro and micro nutrient of soil,improving plant growth and local corn production. Ela sagu compost can remedied sandy soil. The higher dosage until 15 ton per hectare of the compost the higher of growth and productionof corn.